Short-term cardiac autonomic recovery after a repeated sprint test in young soccer players - Cavinato Cal Abad, C.; Adriano Pereira, L.; Zanetti, V.; Kobal, R.; Loturco, I.; Nakamura, F. Y. (Sports, 2019)
The aim of this study was to describe the time course (within 2 h post-exercise) of heart rate variability (HRV) recovery following a traditional repeated sprint ability (RSA) test applied to youth soccer players. Twenty-four young soccer players (18.4 ± 0.5 years) undertook the following assessments: (1) 10 min rest in the seated position for HRV assessment; (2) a repeated sprint ability (RSA) test; (3) passive recovery in the seated position for 10 min, immediately after finishing the RSA test and 1 h and 2 h post-RSA test. During the HRV measurements (using the natural log of root mean square difference of successive normal RR intervals—lnRMSSD) the participants were instructed to assume a comfortable sitting position, remaining awake and breathing spontaneously for 10 min. Magnitude-based inference was used in the analyses. After the RSA test, the post-1 h measure was almost certainly lower than the resting measure, but almost certainly higher than the lnRMSSD measured post-RSA test. The lnRMSSD post-2 h was likely lower than the resting lnRMSSD and very likely higher than post-1 h. In conclusion, lnRMSSD is severely depressed after performing an RSA test, and reactivation is incomplete after 2 h of passive recovery. This result should be considered by practitioners when applying successive training sessions within intervals shorter than 2 h.